Potential safety risks in schools: ensuring the safety of our precious ones - Sambasivam, Sivasankar; Karuppiah, Karmegam; Subramaniam, Kulanthayan; Praveena, Sarva Mangala; Zainal Abidin, Emilia (Wolters Kluwer - Medknow, 2017)
The school has become an inextricable part of the modern society throughout the world and especially in Malaysia. During the weekdays, schools are typically a hive of activities where the adults (teachers and other workers) and children (students) interact with each other daily. Schools often maintain a low-risk level of safety and health. Schools have potential variety of risk and hazards (physical and social) that can negatively affect the wellbeing and health of the people. The Malaysian Department of Safety and Health (DOSH) have issued the Hazard Identification, Risk Assessment and Risk Control (HIRARC) for identifying the risk elements during usual and special operations and to predict the likelihood and severity in workplaces. This study was carried out to identify all the factors and hazards that may cause harm to occupant of a selected school in the state of Selangor, Malaysia. An assessment was carried out to consider the chances of that harm befalling anyone in the circumstances of a particular case and the possible severity of the outcome to enable school administrators to plan, introduce, and monitor preventive measures to ensure that the risks are adequately controlled at all times. The HIRARC assessment on the selected school identified that physical hazard has the highest frequency, followed by ergonomic, biological, chemical, and psychosocial hazards. The kitchen, science laboratory, and toilet are the areas that have higher potential for accident to happen. Although in terms of risk, most of the hazards are categorized under medium followed by low risk, but none of hazards are categorized under the high-risk group. There is a critical need to ensure that the school environment is constantly kept safe and healthy to ensure that the process of lifelong building of knowledge and practices can be sustained for the future of the nation.